UJI KUALITATIF ALKOHOL URINE PEMINUM TUAK DALAM MENGETAHUI WAKTU SAMPLING YANG TEPAT - I Made Suardika; Lale Budi Kusuma Dewi; Thomas Tandi Manu; I Wayan Getas; Ida Bagus Rai Wiadnya (Meditory : The Journal of Medical Laboratory, 2023)
Background:Accidents and criminal acts can be caused by alcohol use. Alcohol use by a person can be known by analyzing a urine sample. In the analysis of urine samples it is necessary to take the right sampling time. In addition, another factor to consider when detecting alcohol in urine is the time of last consumption. Aims:This study was conducted to determine the appropriate urine sampling time for alcohol consumption. Methode:The method used in this urine alcohol qualitative test uses the modified 2.5% potassium bichromate method in 50% H2SO4. The sample consisted of 10 respondents who drank palm wine after 1 hour, 2 hours and 3 hours of consumption. The results:The qualitative test results of urine drinkers of palm wine drinkers after 1 hour, 2 hours and 3 hours of consuming. 10 respondents obtained the results of 4 positive urine samples 1 hour after consuming and 2 positive urine samples 3 hours after consuming palm wine, as well as sampling in the 2nd hour the test results were negative. Conclusion:The positive test results depended on the habit of consuming, the volume consumed, and the age of the wine drinker